2022
DOI: 10.1038/s41419-022-04904-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell characterization of malignant phenotypes and microenvironment alteration in retinoblastoma

Abstract: Retinoblastoma (RB) is the most common primary intraocular malignancy of childhood. It is known that the tumor microenvironment (TME) regulates tumorigenesis and metastasis. However, how the malignant progression in RB is determined by the heterogeneity of tumor cells and TME remains uncharacterized. Here, we conducted integrative single-cell transcriptome and whole-exome sequencing analysis of RB patients with detailed pathological and clinical measurements. By single-cell transcriptomic sequencing, we profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 70 publications
(75 reference statements)
4
24
0
Order By: Relevance
“…To study the genotype of the RB sample, we inferred copy number variations (CNVs) for each cell by averaging relative expression levels across intervals of the genome and calculated the CNV mean square in the control retina and RB samples 15,16 . We found various CNV types in the RB sample, including gain of chromosome (Chr) 1q, 6p and loss of Chr 16 (Figure 1D), consistent with previous studies in human RB 5 . Also, CNV patterns were also conserved across all ten RB clusters.…”
Section: Spatial Transcriptomic Profiling Of Human Rb and Control Retinasupporting
confidence: 91%
See 2 more Smart Citations
“…To study the genotype of the RB sample, we inferred copy number variations (CNVs) for each cell by averaging relative expression levels across intervals of the genome and calculated the CNV mean square in the control retina and RB samples 15,16 . We found various CNV types in the RB sample, including gain of chromosome (Chr) 1q, 6p and loss of Chr 16 (Figure 1D), consistent with previous studies in human RB 5 . Also, CNV patterns were also conserved across all ten RB clusters.…”
Section: Spatial Transcriptomic Profiling Of Human Rb and Control Retinasupporting
confidence: 91%
“…While a majority of children with RB cases stem from biallelic RB1 inactivation, for a minor portion, MYCN amplification is exhibited without RB1 alterations 2,3 . Next-generation sequencing studies have also revealed additional genetic abnormalities beyond RB1 inactivation that are associated with aggressive histopathological features 4,5 , highlighting the complexity of the genetic lesions causing the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinoblastoma is an aggressive intraocular tumor. The regulatory mechanisms of m6A [23], tumor microenvironment [24] and methylation [25] in retinoblastoma have been extensively reported in literature, and the prognosis of retinoblastoma has been predicted. Despite the bioinformatics analysis of retinoblastoma, the existing cuproptosis-related retinoblastoma research is not abundant.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated to account for about 4% of all forms of cancer in children under age of 15. It predominantly impacts infants and young children, and clinical signs are uncommon [4]. A white colour in the pupil can be seen in dim light or when taking a picture with flash named cat's eye reflex or Leukocoria; crossed eyes, the eyes that seem to be looking in different directions termed strabismus, that can end up causing squinting; alter in iris colour; Poor sight, eye strain, reddening, and inflammation, Infection of the eyelids, larger eyeball than normal, the coloured portion of the eye, and pupil apparently cloudy.…”
Section: Introductionmentioning
confidence: 99%